(untitled) (African Journal of Biomedical Research, 2021)
Synthetic anticancer drugs are expensive and toxic; therefore, there has been much interest in developing anticancer agents from natural resources and especially plants. The stem bark of Adansonia digitata (SBAD) has many traditional medicinal uses, including the treatment of cancer, but there is currently little scientific evidence to support this. The aim of this study was therefore to assess the cytotoxic and long term antiproliferative effects of a methanol extract of SBAD (MESBAD) on breast cancer cells. Cold extraction was done on SBAD using 70% methanol for 72 hrs. The extract was filtered, concentrated and lyophilized. MCF-7 breast cancer cells were cultured using an established procedure and were treated with MESBAD or DMSO as control. Cytotoxicity and long-term survival were measured using MTT and clonogenic assays respectively. Western blotting was performed with antibodies against p53 and p21. MESBAD induced short-term and long-term (13 to 15 days) cytotoxicity in breast cancer cells in a dose dependent manner and exhibited an IC50 of 100μM. Western blotting indicated that MESBAD activated the p53 tumour suppressor and its target, p21. MESBAD induces cytotoxicity and inhibits long-term survival of MCF-7 breast cancers cells through a mechanism involving the up-regulation of the cell cycle and cell death regulators p53 and p21.